Le abilità di comprensione del testo in soggetti afasici adulti - Moriconi, Ilaria; Favilla, Maria Elena; Benedetti, Roberta; Cerchi, Giulia; Ferroni, Lucia (CHIMERA: Revista de Corpus de Lenguas Romances y Estudios Lingüísticos, 2022)
Experiences of daily interactions with Italian aphasic subjects with unimpaired comprehension abilities according to standardized aphasia tests raise doubts about their actual and complete understanding of what has been said. The available standardized aphasia tests assess only the comprehension of phonemes and of isolated words and sentences, while no tools specifically developed for aphasics exist for the assessment of multiple sentence utterances and for interactions comparable to everyday real interactions. A more precise assessment of comprehension abilities would be necessary, in order to allow clinicians involved in the treatment of aphasia to develop treatment strategies aimed at improving actual comprehension in everyday interactions, as well as to make predictions and give indications for social and work reintegration after treatment. This paper presents the results of a research developed from the cooperation of clinicians (neurologist, physiatrists, speech therapist) and linguists aimed at collecting data on text and discourse comprehension abilities in 28 Italian aphasic adults with left-hemisphere brain damage presenting good performances in standardized comprehension subtests and 28 comparable non-aphasic adults.